THE POTENTIAL OF LAND VALUE CAPTURE FOR A TRANSIT-ORIENTED DEVELOPMENT INITIATIVE IN PEKALONGAN CITY CENTER - Pradoto, Wisnu; Rahdriawan, Mardwi; Safrul, Muhammad; Ramli, Nurul Anam (Jurnal Pengembangan Kota, 2024)
Investment is a trigger for increasing the economic potential of a region. Land value is an indicator that not only reflects it, but also shows its development prospects. Government applies variety instruments of land use to improve the attractiveness of an area, especially for commercial activities. This study aims to formulate the Land Value Capture model as an innovation for financing the infrastructure development as well as for generating public revenues. Pekalongan City Center, which is located around the railway station, is an economic magnet that contains several advantages for Transit Oriented Development application. This research examines the determinant variables through Multiple Linear Regression. The model shows the significance of each influencing factor to raise land value. The study finds LVC tools that possibly applied. Discussion regarding the lack of financial capacity on government side while developable land is predominated owned by public institution vis-à-vis the needs for involving private investors to optimize the economic potential for new development is interested to understand about the differences between theoretical and practical point of view.